THE EFFECT OF AUDITOR INDEPENDENCE AND EXPERIENCE ON FRAUD DETECTION WITH PROFESSIONAL SKEPTICISM AS MODERATOR - Dwi Mardianto; Rita Yuniarti (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
The primary objective of a financial statement audit is to express the auditor's opinion on whether the statements have been prepared correctly in all material respects, that is, whether the statements are true and objective. Fraud remains a problem today. Fraud can be committed by individuals from within or outside the organization, due to auditors not detecting it. This research aims to analyze the influence of independence and audit experience on fraud detection by considering the role of professional skepticism as a moderator. This research method uses descriptive with a quantitative approach and data analysis techniques used partial least squares (PLS) through SmartPLS software version 4, the sample consisted of 25 public accounting firms in Bandung city with the sampling technique used using saturated sampling and obtained 76 respondents, the results of this study indicate that (Independence and Audit Experience have a significant influence on fraud detection, professional skepticism can moderate independence, professional skepticism cannot moderate audit experience on fraud detections.